Fintech: Good and Bad News for Sustainable Finance - Henderson, Hazel (Pesquisa & Debate Revista do Programa de Estudos Pós-Graduados em Economia Política, 2017)
Today, we need to explore deeper societal issues surrounding the rapid deployment of computerized electronic platforms, cryptocurrencies and algorithms now disrupting legacy financial firms and their models. Such electronic platforms and technologies have been disrupting many sectors of industrial societies since the 1960s’ automation of manufacturing and more recently of publishing, retail, travel, legal and medical services. One of the first financial disruptors was WitCapital, founded by Andrew Klein, described in his book WallStreet.com (1998), which participated in 127 offerings, raised $9 billion and at its peak in 1999 was worth $2 billion. WitCapital was bought by Sound View Technology Group in 2000, and Klein now helps non-profits in his Amsterdam home. Recent applications now disrupting traditional finance are systemic and global, see for example the FINTECH 100 and the rush to use Blockchainbased ledgers both to protect incumbents’ markets and to disrupt them. All this is described in depth, as well as with broad global analyses in Blockchain Revolution by Don and Alex Tapscott (2016), the most comprehensive overview so far of blockchain’s promise, future and policy implications. The core issue in finance is trust, on which all markets rely, and these distributed ledgers offer many new ways of verifying transactions, ownership, legal rights, identity and reputations so as to restore trust in many systems. The new topologies and networks reshaping earlier human trust relationships with protocols, principles, standards and gated sites are described by Joshua Cooper Ramo in The Seventh Sense (2016). Research by Venture Scanner tracked 1,379 fintech companies in March 2016 with combined funding of $33 billion. The Chamber of Digital Commerce, founded by Perianne Boring is leading in convening fintech companies and how standards and applications to regulations and government functions are evolving (www.digitalchamber.org).